A test to measure students' systems thinking abilities in geography - Marjolein COX; Jan ELEN; An STEEGEN (European Journal of Geography)
In high school geography students are taught about complex geospatial relations that often focus on the interaction between humans and their environment. Systems thinking as an approach concentrates in general on understanding interconnections between variables in a system to see the bigger picture. Therefore systems thinking is an appropriate approach in  geography education. Recently it is also seen as an important cognitive skill in some European countries. However, an appropriate tool to assess systems thinking in geography is currently missing. In this article, a test and its development are described. The test was administered with 617 students of 16 to 18 years old in secondary education in Flanders. Based on the validation process, the reliability measures and the distribution of the students’ scores, it is concluded that the proposed test is a valid and reliable assessment instrument for future research.